Characteristics of lactic acid bacteria isolated from palm sugar from West Sumatra, Indonesia and their potential as a probiotic - NURAZIZAH RAMADHANTI; SRI MELIA; JAMES HELLYWARD; ENDANG PURWATI (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ramadhanti N, Melia S, Hellyward J, Purwati E. 2021. Characteristics of lactic acid bacteria isolated from palm sugar from West Sumatra, Indonesia and their potential as a probiotic. Biodiversitas 22: 2610-2616. Palm sugar is one of the sugar products from palm sap processing. It is made by reducing the water content in the sap to certain water content and is used as a natural sweetener. This study used palm sugar from 3 producers, i.e. Marapalam Gula Semut (MGS), Tetesan Gula Semut (TGS) and Sungayang Gula Semut (SGS) in Sungayang, West Sumatra, Indonesia. This study aimed to isolate and identify lactic acid bacteria (LAB) from palm sugar, potentially as a probiotic, using the 16S rRNA method. The probiotic potential of bacteria was selected based on morphology, biochemical properties, resistance to acidic pH 3 and 0.3% bile salts, antimicrobial activity against pathogenic bacteria. The results showed that lactic acid bacteria isolated from palm sugar are Gram-positive rod-shaped (Bassil), negative catalase, and homofermentative. The total colonies of lactic acid bacteria ranged from 50 x 107 cfu/g - 117 x 107 cfu/g. The MGS lactic acid bacteria had 74.71% viability resistance in acidic pH 3, 65.52% viability against bile salts (0.3% ox gall). The diameter of inhibition against Escherichia coli O157 was 18.20 mm, Propionibacterium acnes (18.00 mm), Acinetobacter baumannii (14.19 mm), and Listeria monocytogenes (16.35 mm). The phylogenetic tree based on 16S rRNA showed that the MGS isolate has a similarity of 99.92% to Lactobacillus fermentum strain 1743. It can be concluded that Lactobacillus fermentum strain 1743 isolated from palm sugar has potential as a probiotic.